2007
DOI: 10.1159/000101411
|View full text |Cite
|
Sign up to set email alerts
|

Role of RIG-I, MDA-5, and PKR on the Expression of Inflammatory Chemokines Induced by Synthetic dsRNA in Airway Epithelial Cells

Abstract: Background: We hypothesized that synthetic double-stranded (ds)RNA may mimic viral infection and reported that dsRNA stimulates expression of inflammatory chemokines through a receptor of dsRNA Toll-like receptor (TLR) 3 in airway epithelial cells. In this study, we focused our study on the role of other receptors for dsRNA, such as retinoic acid-inducible gene I (RIG-I), melanoma differentiation-associated gene 5 (MDA-5), and double-stranded RNA-dependent protein kinase (PKR). Methods: Airway epithelial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…A synthetic dsRNA, poly(I:C), has been used extensively as a surrogate for viral dsRNA to study host responses. It provokes inflammatory and interferon (IFN) responses in airway epithelial cells, similar to viral dsRNA (4,30,49). Recently, dsRNA was also shown to decrease R T in immortalized nasal epithelial cells (35), but the underlying mechanism was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthetic dsRNA, poly(I:C), has been used extensively as a surrogate for viral dsRNA to study host responses. It provokes inflammatory and interferon (IFN) responses in airway epithelial cells, similar to viral dsRNA (4,30,49). Recently, dsRNA was also shown to decrease R T in immortalized nasal epithelial cells (35), but the underlying mechanism was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that RV-induced Rac1-dependent NOX1 activity is required to disrupt barrier function. We also show that polyinosinic-poly(C) [poly(I:C)], a synthetic analog of double-stranded RNA (dsRNA) that has been used to examine viral dsRNA-stimulated responses in airway epithelial cells (26,30,49), impairs barrier function by a mechanism similar to that of RV, indicating that dsRNA generated during replication contributes to the disruption of barrier function.…”
mentioning
confidence: 99%
“…4E), which demonstrated the essential role of TLR3 in the cell's response to poly(I-C). Several studies have confirmed the importance of TLR3, RIG-I, or MDA-5 in poly(I-C) recognition (19,21,26,27), and the question of whether RIG-I or TLR3 predominantly recognizes poly(I-C) in cells remains unresolved. Based on our results that p53 affects the expression of TLR3 but not that of MDA-5 or RIG-I, it is tempting to speculate that the activation of these pattern recognition receptors by poly(I-C) may, in part, depend on the p53 status of cells or tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Expression was observed in our mice early in infection and was maximal at day 8 when strong immunoreactivity in epithelial cells lining the airways and in mononuclear cells was obvious. Pulmonary epithelial cells express TLR3 (46,68) and PKR (46,68,69). S100A8 is up-regulated in bronchial epithelial cells by LPS (3) and S100A8/S100A9 is expressed in tracheal epithelial cells from patients with cystic fibrosis (70).…”
Section: Discussionmentioning
confidence: 99%